UPAYA HUKUM INDONESIA DALAM MENANGGULANGI MASALAH PEKERJA MIGRAN INDONESIA DILUAR NEGERI YANG MELEBIHI BATAS IZIN TINGGAL (OVERSTAYERS) (Studi Kasus Pekerja Migran Indonesia di Kerajaan Arab Saudi) - Aisyah Wulandari (2023)
Several problems arose along with the migration process to the Kingdom of Saudi Arabia. One of the most crucial problems is the problem of Indonesian migrant workers in Saudi Arabia but do not comply with the residence permit procedures. The number of PMIs in Saudi Arabia who have exceeded the limit for their residence permits (overstayers) has reached thousands. Various efforts to protect the law have been attempted by the Indonesian state, but in reality many Indonesian citizens do not comply with applicable regulations by distorting procedures and not following the regulations regarding labor migration that have been in effect in Saudi Arabia. Factors that cause PMI overstay also vary, ranging from problems related to unprocedural and problems related to undocumented. The Government of Indonesia has implemented legal remedies in various activities and assistance for PMI overstayers in Saudi Arabia, including deportation efforts, amnesty requests, legal reforms, realization of the SPSK (One Channel Placement System) program, and the passportization program. Through the empirical normative type method, this research tries to describe the primary data from the legislation and the views and doctrines of the prevailing jurisprudence. Secondary data is presented related to the number of PMIs with official documents, the number of PMI placement and protection in Saudi Arabia, and the number of successes of the Indonesian government in assisting the repatriation of overstayed PMIs in Saudi Arabia.